2008
DOI: 10.2353/ajpath.2008.070572
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of Lymphotoxin in T Cells Induces Fulminant Thymic Involution

Abstract: Activated lymphocytes and lymphoid-tissue inducer cells express lymphotoxins (LTs), which are essential for the organogenesis and maintenance of lymphoreticular microenvironments. Here we describe that Tcell-restricted overexpression of LT induces fulminant thymic involution. This phenotype was prevented by ablation of the LT receptors tumor necrosis factor receptor (TNFR) 1 or LT beta receptor (LT␤R), representing two non-redundant pathways. Multiple lines of transgenic Lt␣␤ and Lt␣ mice show such a phenotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
21
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 65 publications
5
21
0
Order By: Relevance
“…Tg Lck-LTαβ mice develop a fulminant thymus involution that is dependent on LTα 3 /TNFR1 and LTα 1 β 2 /LTβR signaling within the cTEC recapitulating virus infection-related thymic involution by activated LTαβ-overexpressing T cells. 44,45 Therefore, to assess the role of NIK in cell death of cTEC, we performed bone marrow (BM) reconstitution assays using WT or Tg Lck-LTαβ mice as donors and WT or aly/aly NIK-deficient recipient mice. 46 For phenotypic analyses, 8 weeks postreconstitution mice were killed and thymi were imaged and quantitatively and qualitatively analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Tg Lck-LTαβ mice develop a fulminant thymus involution that is dependent on LTα 3 /TNFR1 and LTα 1 β 2 /LTβR signaling within the cTEC recapitulating virus infection-related thymic involution by activated LTαβ-overexpressing T cells. 44,45 Therefore, to assess the role of NIK in cell death of cTEC, we performed bone marrow (BM) reconstitution assays using WT or Tg Lck-LTαβ mice as donors and WT or aly/aly NIK-deficient recipient mice. 46 For phenotypic analyses, 8 weeks postreconstitution mice were killed and thymi were imaged and quantitatively and qualitatively analyzed.…”
Section: Resultsmentioning
confidence: 99%
“…As previously reported, reconstitution of Lck-LTαβ BM into WT recipient mice led to a drastic reduction in thymus size compared with the reconstitution of WT BM into WT recipient mice (Figure 5a). 44 Reciprocal reconstitution experiments using Lck-LT αβ BM into aly/aly recipient mice greatly protected from LTαβ-induced thymus involution. Indeed, thymi were comparable in size to those obtained from reconstitution experiments of WT BM into WT recipient mice or aly/aly BM into aly/aly recipient mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of LT in the context of lymphoid neogenesis, development of autoimmune diseases and inflammatory disorders was further investigated in vivo (Picarella et al, 1992;Kratz et al, 1996;Luther et al, 2000;Drayton et al, 2003Drayton et al, , 2006Gommerman and Browning, 2003;Martin et al, 2004;Heikenwalder et al, 2005Heikenwalder et al, , 2008Haybaeck et al, 2009). These studies revealed that ectopic LT expression suffices to generate lymphoid-like structures (Picarella et al, 1992;Kratz et al, 1996;Gommerman and Browning, 2003;Heikenwalder et al, 2005;Haybaeck et al, 2009), also termed tertiary lymphoid organs or tissues.…”
Section: Lt and Inflammationmentioning
confidence: 99%